The fluid content of the human intervertebral disc. Comparison between fluid content and swelling pressure profiles of discs removed at surgery and those taken postmortem. - Johnstone, B; Urban, J; Roberts, S; Menage, J (1992)
The fluid content of the disc, which governs its mechanical response and biological behavior, varies with external load. Because load on the disc changes after death, the fluid content and swelling pressure profiles of human discs taken at autopsy were measured, and compared with discs removed during surgical procedures. In general, discs taken at surgery had a lower fluid content in the nucleus and a higher fluid content in the outer anulus than discs removed at autopsy. In discs removed at surgery, the swelling pressure of the nucleus was higher than that of the anulus, whereas in autopsy discs the swelling pressure profile was flat. These changes are though to result from changes in load after death, and could influence the results of in vitro mechanical tests on the disc.